Mathematical Methods in Chemical & Environmental Engineering - Ajay Ray (Thosmson Asia, 2003)
This comprehensive book covers a broad selection of mathematical topics that are essential for a modern chemical/environmental engineer. It features a blend of analytical and numerical techniques for solving problems in diverse areas, such as, heat and mass transfer, thermodynamics, fluid mechanics, reaction engineering, transport phenomena, and process systems engineering. This new text emphasizes problem-solving, and deals extensively with methods for solving systems of linear and non-linear algebraic equations, systems of linear and non-linear ordinary and partial differential equations. Students in chemical and environmental engineering would find this book useful for their undergraduate and post-graduate courses. It can also be used as a reference book for research students involved in computational work, or even as a text in other related engineering areas involving computational activities and analytical concepts